Financial Globalization and Exchange Rates - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper, 2005)
The founders of the Bretton Woods System 60 years ago were primarily concerned with orderly exchange rate adjustment in a world economy that was characterized by widespread restrictions on international capital mobility. In contrast, the rapid pace of financial globalization during recent years poses new challenges for the international monetary system. In particular, large gross cross-holdings of foreign assets and liabilities mean that the valuation channel of exchange rate adjustment has grown in importance, relative to the traditional trade balance channel. Accordingly, this paper empirically explores some of the interconnections between financial globalization and exchange rate adjustment and discusses the policy implications.